Factors Influencing Sleep Quality Among Elderly At Geriatric Residence Of Rindang Asih Ungaran Semarang - S Hudijono; Budi Widiyanto (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
The objective of this study was to describe sleep quality and identify factors influencing sleep quality among elderly at geriatric residence of Rindang Asih , Ungaran, Semarang. The research design was descriptive study, using purposive sampling. 20 elderly at geriatric residence are being respondent in this study. Collecting data used Pittsburgh Sleep Quality Index and factors influencing sleep quality check list which made by the researcher. The research result has shown poor quality of elderly at geriatric residence of Rindang Asih , Ungaran, Semarang dominant in this setting and it was dominated by elderly on 75 years old or older. Sleep quality in this setting was influenced by age, physical illness, activity, anxiety, and physical environment. The health care provider should know the sleep problems, sleep necessary and habitual sleep of patients by assessment so that a good intervention for the clients can be performed satisfactorily.